Smart Farming: Enhancing Network Infrastructure for Agricultural Sustainability - Mishra, Vaibhav; Pandey, Ankit; Vangari, Lakitaa; Khanam, Shaista (Journal of Ubiquitous Computing and Communication Technologies, 2024)
In addressing the critical challenge of feeding an ever-expanding global population, smart farming emerges as a beacon of hope, despite encountering ongoing issues such as farmers’ resistance to adopting new technologies. The approach involves leveraging cutting-edge technology and IoT devices, including various sensors for farm maintenance and monitoring, even in the absence of farmers, through our website. A persistent challenge arises in updating smart farms, particularly in networking capabilities, as they currently lack the adaptability to 4G or 5G. This also causes problems in monitoring real-time data on crucial parameters such as soil moisture, weather conditions, and the absence of a monitoring system on a farm can lead to inefficiencies in resource management, as well as delayed responses to emergencies, impacting overall productivity and sustainability. To overcome this, the proposed study offers a solution by integrating an ESP32 equipped with 4G LTE connectivity. This will provide farmers with real-time data and insights, ensuring appropriate connectivity and enabling robust, high-speed data transmission for farming practices. Moreover, providing solar panel connectivity for power supply further enhances the sustainability and autonomy of these systems. By harnessing renewable energy sources, the proposed method not only ensures continuous operation but also contributes to reducing the environmental footprint of agricultural operations. This innovation holds the potential to revolutionize traditional farming methods, paving the way for a more sustainable and productive agricultural future on a global scale.